Theoretical Problems of Legal Regulation of Innovations in the Medical Field: Experience in Counteracting Covid-19 - Федоров, Валентин Андрійович; Федоров, Валентин Андреевич; Fedorov, Valentyn A.; Кравченко, Сергій Петрович; Кравченко, С. П.; Кравченко, Сергей Петрович; Kravchenko, Serhii P.; Kravchenko, Sergii; Резніченко, Ганна Семенівна; Резніченко, Г. С.; Резниченко, Анна Семеновна; Reznichenko, Hanna S.; et al. (Quito : Hemisferios University, 2020)
The work is devoted to identifying the main problems of legal regulation of innovations in the medical field and developing the best options for solving them in the context of the Covid-19 pandemic. Thus, the research methodology is based on general and special scientific methods, in particular: formal legal, historical and legal, comparative analysis, and modeling. So, the procedure and issues to be considered are as follows. In the introduction, we will briefly highlight the origins of intellectual property rights issues in the medical field and the overall state of the pharmaceutical industry. In the first subsection of the third section, we will consider the positions of the main players in the pharmaceutical industry and the contradictions between them. In the second subsection, we will highlight the international obligations under TRIPS. In the third subsection, we will consider the consequences of their direct violation. In the fourth subsection, the impact of Covid-19 and the methods of legal regulation of medical innovations and patents under the TRIPS agreement will be discussed. In the fifth subsection, we will propose a way out and a compromise according to the Indian scenario. As a result of the study, contradictions were identified in the aspect of maintaining the balance of private and public interests between states and international pharmaceutical companies in the context of a pandemic and proposed ways to resolve them within the existing legal methods under the TRIPS agreement to achieve an acceptable compromise.

Робота присвячена визначенню основних проблем правового регулювання інновацій у медичній сфері та розробці оптимальних варіантів їх вирішення в умовах пандемії Covid-19. Таким чином, методологія дослідження базується на загальнонаукових і спеціально-наукових методах, зокрема: формально-правовому, історико-правовому, порівняльному аналізі та моделюванні. Отже, порядок і питання, які мають бути розглянуті, такі. У вступі ми коротко висвітлимо витоки проблем прав інтелектуальної власності в медичній сфері та загальний стан фармацевтичної промисловості. У першому підрозділі третього розділу ми розглянемо позиції основних гравців у фармацевтичній галузі та суперечності між ними. У другому підрозділі ми виділимо міжнародні зобов’язання за ТРІПС. У третьому підрозділі ми розглянемо наслідки їх прямого порушення. У четвертому підрозділі буде розглянуто вплив Covid-19 та методи правового регулювання медичних інновацій та патентів за угодою TRIPS. У п’ятому розділі ми запропонуємо вихід і компроміс за індійським сценарієм. У результаті дослідження виявлено суперечності в аспекті підтримки балансу приватних та державних інтересів між державами та міжнародними фармацевтичними компаніями в умовах пандемії та запропоновано шляхи їх вирішення в рамках існуючих правових методів згідно з угодою TRIPS до досягти прийнятного компромісу.
Fedorov V. Theoretical Problems of Legal Regulation of Innovations in the Medical Field: Experience in Counteracting Covid-19 / V. Fedorov, S. Kravchenko, H. Reznichenko, N. Opara, O. Tsybokhin // Ius Humani. Law Journal. - Vol. 9. - Issue 2. - Quito : Hemisferios University, 2020. - P. 251-289.
Keywords: innovation; coronavirus; intellectual property; health; TRIPS Agreement; інновації; коронавірус; інтелектуальна власність; охорона здоров'я; Угода TRIPS; Research Subject Categories::LAW/JURISPRUDENCE